1988
DOI: 10.1002/em.2860120305
|View full text |Cite
|
Sign up to set email alerts
|

Increased sister chromatid exchange associated with smoking and coffee consumption

Abstract: Sister chromatid exchange (SCE) is a very sensitive cytogenetic assay for detecting exposure to chemical mutagens and carcinogens. One application of SCE is the monitoring of populations believed to be exposed to such agents. We have, however, relatively little knowledge about common lifestyle factors that may influence SCE and therefore complicate any study designed to examine the effects of exposure to genotoxins. In this study, we assessed the effect of cigarette smoking and coffee consumption on SCE. Smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 29 publications
4
6
0
1
Order By: Relevance
“…However, the present authors found a time-dose-effect relationship between smoking and the frequency of CA in hookah smokers (Yadav & Thakur, 2000). The present report of significant increase in the frequency of SCE in the lymphocytes of bidi smokers agrees with several earlier findings of increased frequency of SCE in the lymphocytes of cigarette smokers (Ardito et al, 1980;Bala Krishna Murthy, 1979;Carrano, 1982;Crossen & Morgan, 1980;Ghosh & Ghosh, 1988;Hedner et al, 1983;Hollander et al, 1978;Hopkin & Evans, 1980;Husgafvel-Pursiainen et al, 1980;Husum et al, 1982;Kao-Shan et al, 1987;Lambert, 1978;Livingston & Fineman, 1983;Lundberg & Livingston, 1983;Parodi et al, 1982;Reidy et al, 1988;Reuterwall, 1990;Wulf, Husum, & Niebuhr, 1983;Yadav & Kaushik, 1996, 1997Yadav & Seth 1998a, 1998b. The increase in SCE recorded in the present study (from 3.68 to 7.65) agrees with the results reported by the present authors in the lymphocytes of hookah smokers (from 3.59 to 5.66).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the present authors found a time-dose-effect relationship between smoking and the frequency of CA in hookah smokers (Yadav & Thakur, 2000). The present report of significant increase in the frequency of SCE in the lymphocytes of bidi smokers agrees with several earlier findings of increased frequency of SCE in the lymphocytes of cigarette smokers (Ardito et al, 1980;Bala Krishna Murthy, 1979;Carrano, 1982;Crossen & Morgan, 1980;Ghosh & Ghosh, 1988;Hedner et al, 1983;Hollander et al, 1978;Hopkin & Evans, 1980;Husgafvel-Pursiainen et al, 1980;Husum et al, 1982;Kao-Shan et al, 1987;Lambert, 1978;Livingston & Fineman, 1983;Lundberg & Livingston, 1983;Parodi et al, 1982;Reidy et al, 1988;Reuterwall, 1990;Wulf, Husum, & Niebuhr, 1983;Yadav & Kaushik, 1996, 1997Yadav & Seth 1998a, 1998b. The increase in SCE recorded in the present study (from 3.68 to 7.65) agrees with the results reported by the present authors in the lymphocytes of hookah smokers (from 3.59 to 5.66).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, many authors reported a smoke-related increase in the frequency of sister chromatid exchanges (SCE) (Bala Krishna Murthy, 1979;Carrano, 1982;Ghosh & Ghosh, 1988;Hopkin & Evans, 1980;Husgafvel-Pursiainen, 1987;Husum, Wulf, & Niebuhr, 1982;Kao-Shan, Fine, Whangpeng, Lee, & Chalnor, 1987;Lambert, Lindblad, Nadensbjold, & Werelius, 1978;Livingston & Fineman, 1983;Lundberg & Livingston, 1983;Obe & Herha, 1978;Parodi, De Ferrari, Ottoggio, Zunino, & Santi, 1982;Reidy, Chen, & Welty, 1988;Wulf, Husum, & Niebuhr, 1983). However, others did not find such an increase (Ardito, Lamberti, Ansakli, & Ponzetto, 1980;Crossen & Morgan, 1980;Hedner, Hogstedt, Kolnig, Mark-Vendal, Strobeck, & Mitelman, 1983;Hollander, Tockman, Lian, Borgaokar, & Frost, 1978).…”
Section: Introductionmentioning
confidence: 98%
“…This effect was also observed in other cell types. 15,25,36,37,50,51 The observation that the heaviest smokers showed a higher number of MNs than nonsmokers supports this suggestion and could indicate a dose-dependent effect. This suggestion is supported by the observation that MN occurrence in nonsmokers and smokers of a few cigarettes per day was not different.…”
Section: Discussionsupporting
confidence: 69%
“…A heparinized whole-blood sample (0.3 mL) ing and alcohol consumption [da Cruz et al, 1994]. Rewas added to 4.7 mL of culture medium composed of 4.025 mL Ham's ports on the possible effects of coffee and alcohol intake F10 medium (ICN, Irvine, CA) supplemented with 0.5 mL (10%) fetal are scant and the conclusions largely discordant [Obe and calf serum (ICN), 0.075 mL (1.5%) phytohemagglutinin (PHA, Wellcome, Pomezia, Italy) and antibiotics (100 IU penicillin and 100 mg/ml Ristow, 1979;Obe et al, , 1980Reidy et al, 1988; streptomycin; Sigma, St. Louis, MO). Sarto et al, 1987;Nordic Study Group, 1990;Köteles et al, 1993;Nehlig and Derby, 1994].…”
Section: Introductionmentioning
confidence: 99%